Unstable Gaze in Functional Dizziness: A Contribution to Understanding the Pathophysiology of Functional Disorders - Schröder, Lena; von Werder, Dina; Ramaioli, Cecilia; Wachtler, Thomas; Henningsen, Peter; Glasauer, Stefan; Lehnen, Nadine (Frontiers in Neuroscience, 2021)
Objective: We are still lacking a pathophysiological mechanism for functional disorders explaining the emergence and manifestation of characteristic, severely impairing bodily symptoms like chest pain or dizziness. A recent hypothesis based on the predictive coding theory of brain function suggests that in functional disorders, internal expectations do not match the actual sensory body states, leading to a perceptual dysregulation and symptom perception. To test this hypothesis, we investigated the account of internal expectations and sensory input on gaze stabilization, a physiologically relevant parameter of gaze shifts, in functional dizziness. Methods: We assessed gaze stabilization in eight functional dizziness patients and eleven healthy controls during two distinct epochs of large gaze shifts: during a counter-rotation-epoch (CR-epoch), where the brain can use internal models, motor planning and resulting internal expectations to achieve internally-driven gaze stabilization, and during an oscillation-epoch (OSC-epoch), where, due to terminated motor planning, no movement expectations are present, and gaze is stabilized by sensory input alone. Results: Gaze stabilization differed between functional patients and healthy controls only when internal movement expectations were involved (F(1,17) = 14.63, p = 0.001, partial eta2 = 0.463): Functional dizziness patients showed reduced gaze stabilization during the CR- (p = 0.036) but not OSC-epoch (p = 0.26). Conclusions: While sensory-driven gaze stabilization is intact, there are marked, well measurable deficits in internally-driven gaze stabilization in functional dizziness pointing at internal expectations that do not match actual body states. This experimental evidence supports the perceptual dysregulation hypothesis of functional disorders and is an important step towards understanding the underlying pathophysiology.